Deliberate Practice as a Theoretical Framework for Interprofessional Experiential Education - Wang, Joyce M.; Zorek, Joseph A. (Frontiers in Pharmacology, 2016)
Objective: The theory of deliberate practice has been applied to many skill-based performance activities. The primary aim of this project was to integrate synergistic principles from deliberate practice and consensus-derived competencies for interprofessional education into a framework upon which educational models to advance interprofessional experiential education (IEE) might be built. Methods: CINAHL, ERIC, and MEDLINE databases were searched using the keywords “deliberate practice” and “interprofessional education,” both individually and in combination. Relevant articles were selected from the catalogue based on support for the premise of the project. Defining characteristics of deliberate practice were distilled with particular emphasis on their application to the Interprofessional Education Collaborative’s (IPEC) core competencies. Recommendations for IEE development were identified through the synthesis of deliberate practice principles and IPEC competencies. Results: There is a high degree of synergy between deliberate practice principles and IPEC competencies. Our synthesis of the literature yielded a cyclical four-step process to advance IEE: (1) implement an IEE plan guided by the student’s strengths/weaknesses and in consideration of the collaborative practice skills they wish to develop, (2) engage in IPE experiences that will challenge targeted skills according to the IEE plan, (3) embed frequent opportunities for student reflection and preceptor/team feedback within IEE plan, and (4) revise the IEE plan and the IPE experience based on insights gained during step 3. Conclusion: The cyclical four-step process synthesized through this literature review may be used to guide the development of new IEE models. The purposeful development of IEE models grounded in a theory that has already been operationalized in other skill-based performance areas is an important step to address expanding accreditation standards throughout the health professions mandating interprofessional education for pre-licensure health professional students.